2021
DOI: 10.1038/s41598-021-93922-1
|View full text |Cite
|
Sign up to set email alerts
|

Life experience rather than domestication accounts for dogs’ increased oxytocin release during social contact with humans

Abstract: Dogs’ increased human-directed sociability compared to wolves may be the result of increased oxytocin system activity and decreased stress responses, but comparative studies accounting for life experience are lacking. We compared hand-raised, pack-living wolves’ and dogs’ behavior and hormone concentrations after interacting with a closely bonded and a familiar human. Both preferred the bonded partner, but dogs showed less variability in human-directed sociability than wolves. Physical contact was not associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 75 publications
1
19
0
Order By: Relevance
“…To shed light on the mechanisms of canine social susceptibility, the same experimental paradigm was used to test the effect of intranasal oxytocin treatment. It has been suggested that positive social interactions with the owner increase endogenous oxytocin levels of both the dogs and their owners [21][22][23], although recent research suggest that such effects are conditional on the life experiences of the individuals [24]. At the same time, intranasal oxytocin administration has been shown to influence many aspects of dogs' social behaviour (e.g., affiliative behaviour [25], positive expectation bias [26], use of human pointing [27], processing of emotional faces [28], gazing and social proximity [24]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To shed light on the mechanisms of canine social susceptibility, the same experimental paradigm was used to test the effect of intranasal oxytocin treatment. It has been suggested that positive social interactions with the owner increase endogenous oxytocin levels of both the dogs and their owners [21][22][23], although recent research suggest that such effects are conditional on the life experiences of the individuals [24]. At the same time, intranasal oxytocin administration has been shown to influence many aspects of dogs' social behaviour (e.g., affiliative behaviour [25], positive expectation bias [26], use of human pointing [27], processing of emotional faces [28], gazing and social proximity [24]).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that positive social interactions with the owner increase endogenous oxytocin levels of both the dogs and their owners [21][22][23], although recent research suggest that such effects are conditional on the life experiences of the individuals [24]. At the same time, intranasal oxytocin administration has been shown to influence many aspects of dogs' social behaviour (e.g., affiliative behaviour [25], positive expectation bias [26], use of human pointing [27], processing of emotional faces [28], gazing and social proximity [24]). Thus, we hypothesised that dogs' social susceptibility would be influenced in the same way by both the owner's social stimulation as well as intranasal oxytocin.…”
Section: Introductionmentioning
confidence: 99%
“…It is notable that the concentrations we report are lower than those reported with some other methods. For example, Wirobski, Range, et al (2021) reported pet dog concentrations in the range of 77 – 1500 pg/ml (Mean ± SD = 440 ± 290) before correcting for specific gravity (SG), and 130 – 950 pg/ml (Mean ± SD = 430 ± 190) after doing so. The dog pool that we used for both parallelism and spike recovery analyses had concentrations of 40 – 50 pg/ml (no SG correction), and in another study in progress, pet dog samples have generally measured < 100 pg/ml before SG-correction, and typically < 250 pg/ml after SG-correction.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Marshall-Pescini et al (2019) found that affiliative physical contact between dogs and people did not produce consistent changes in uOT levels measured in either the dogs or their owners. Wirobski, Range, et al (2021) found that in pet dogs, uOT was associated with physical contact with their owner; however, in hand-raised but pack-living dogs and wolves, there was no association between measured uOT and physical contact with a bonded human, suggesting the importance of the animal’s life experience and the strength of the human-animal bond.…”
Section: Introductionmentioning
confidence: 85%
“…This was unexpected since OT has often been associated with sociability, friendliness, and docility toward humans in many species, particularly in assistance animals [38,56,85]. The OT system was suggested to be involved in the dog domestication process [86,87], including if a recent study in dogs and wolves showed that life experience was more influential on OT levels than domestication, showing a positive correlation between the physical contact with the owners and the OT concentrations [88]. The AD involved in our study have a different lifestyles and life experience compared to PD; they undergo repeated separations from their foster family (that fostered them during their first year of age and then on the weekend during their training) every Monday as part of their 6-8 months-long training; from Monday to Friday, they are trained and performed different activities/exercises during the day, and at night they stay in a kennel at the guide school.…”
Section: Free and Total Oxytocinmentioning
confidence: 99%